Developments in the Treatment of Pediatric Long Bone Shaft Fractures - Lieber, Justus; Schmittenbecher, Peter (European Journal of Pediatric Surgery, 2013)
Shaft fractures of the long bones are among the most common pediatric injuries. They are characterized by a limited potential for spontaneous correction because of the fractures—distance to the physis. Although conservative treatment has been practiced for many years with satisfying results, several aspects have led to an increase in the numbers of surgical procedures including changes of living, sports habits, economics, and patients—request to treatment. We reviewed the literature to describe developments of treatment concepts of pediatric shaft fractures. In shaft fractures of the upper extremities, increasing rates of surgical procedures have been reported preventing functional deficits of forearm prosupination and cosmetic deformities of the humerus. In fractures of the lower extremities maximizing stability shifted into the focus of interest to achieve early mobilization and to compensate heavier body weights of children and adolescents. Consecutively, the current gold standard of pediatric shaft fracture treatment—ESIN (elastic stable intramedullary nailing)—has been modified repeatedly using end caps, prebended nails, and optimized surgical techniques. In addition, new methods such as rigid locking nails and plates have been included in the treatment approaches for femur and tibia shaft fractures. All these methods of pediatric fracture care carry inherent advantages that require consideration for each clinical situation. On the other side, this has enlarged the spectrum of potential complications, which needs continuous evaluation to further improve treatment results.
Keywords: pediatric trauma; shaft fractures; elastic stable intramedullary nailing; complications; long bones